Regional Differences of Guillain-Barré Syndrome in China: From South to North - Yao, Jiajia; Liu, Yin; Liu, Shuping; Lu, Zuneng (Frontiers in Aging Neuroscience, 2022)
Abstract Background The epidemiological features of Guillain-Barré syndrome (GBS) were different in different area, comparison of the disease was needed to identify the variation and prognosis. We compare the epidemiological features of GBS in different areas in China. Method A total of 1,191 patients were included. Information was collected in patients diagnosed with GBS and its variants in middle and south China, and then retrospectively reviewed. Patients were divided into four different regions: East China(n=441), Center China(n=566), South China(n=77) and Southwest China(n=107). These subregions are mainly divided by climate and geographical location. This data was compared with data from a study in East China (Shandong, n=150) and Northeast China (Changchun, n=750). Results Patients from south and southwest China were younger than other regions (P=0.000). A summer and autumn peak were found in northern China but more patients in winter and spring days in other areas(P=0.000). Upper respiratory tract infection (URTI) was the main preceding events in all regions but rarer in center China(P=0.001). The proportion of axonal subtype was higher in center and southwest China than in other regions(P=0.001). Patients in southwest China were more serve at nadir and have the longest hospital stay (P=0.003 and P=0.000). Conclusion Seasonal variation and preceding events difference were found in different regions in China, clinical features differ among regions in China.